Red Institucional de Transparencia y Anticorrupción "RITA" y el Control Fiscal en Colombia (2022)
The Institutional Network of Transparency and Anticorruption R.I.T.A., was created by the vice presidency of Colombia in conjunction with all the control entities of the country to be used as an effective and efficient anti-corruption channel. This research work is based on the objective of interpreting the importance of R.I.T.A. in conjunction with fiscal control, of course, a documentary investigation is carried out, taking as sources different pages of public and private entities. A documentary-type investigation is being developed, through which information is captured through books, magazine articles, newspaper articles, newspaper archives, pages of the ministries and publications of the Institutional Network, among others. Finally, it is denoted that the State is determined to create tools that help reduce the margin of corruption, both internal and external, latent in its different dependencies. The idea is to continue to carry out effective fiscal control.